2021
DOI: 10.11591/ijeecs.v22.i2.pp678-687
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Quranic topics based on imbalanced classification

Abstract: Imbalanced classification techniques have been applied widely in the field of data mining. It is used to classify the imbalanced classes that are not equal in the number of samples. The problem of imbalanced classes is that the classification performance tends to the class with more samples while the class with few samples will obtain poor performance. This problem can be occurred in the Qur’anic classification due to the different number of verses. Many studies classified Qur’anic verses, which depended on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Within this type of research, the researchers can compare two or more algorithm to extract the most valuable information inside the Quran. Several text mining studies on Quran explored and analyzed the classification of its content as reported by [12]- [16]. Another type of research in Quran text mining is focus in the specific dataset and analyzing the text mining result acted to the datasets, which are Indonesian Tafseer and Translation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within this type of research, the researchers can compare two or more algorithm to extract the most valuable information inside the Quran. Several text mining studies on Quran explored and analyzed the classification of its content as reported by [12]- [16]. Another type of research in Quran text mining is focus in the specific dataset and analyzing the text mining result acted to the datasets, which are Indonesian Tafseer and Translation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The GOS algorithm was evaluated on 8 binary Quranic datasets with different imbalance ratios. The Quranic datasets were applied by other studies [9][10][11] that were extracted from the Quranic Index collected by Dr Abu Akhir [12]. Table I presents these datasets with their imbalanced ratios and the number of verses in the majority and minority classes.…”
Section: A Datasetsmentioning
confidence: 99%
“…Tabel 6. Analisis Metode Representasi Teks dalam Arabic Natural Language Processing Metode Untuk Representasi Teks Peneliti Jumlah TF-IDF [4], [9], [48], [30], [23], [24], [29], [53], [54], [7], [38], [55], [32], [56], [25], [31], [59], [1], [51], [60] 20 Word2Vec [34], [24], [49], [7], [57], [39], [41], [43], [45], [46] 10 AraVec [34], [35], [37], [40], [41], [42] 6 FastText [34], [47], [35], [57], [41], [42], [50], [46] 8 mBERT [27], [22], [41], [46] 4 AraBERT [36],…”
Section: Tahap Pembuatan Rencana Awalmentioning
confidence: 99%
“…Untuk lebih mempertimbangkan konteks kata dan makna kalimat dapat diatasi dengan dynamic atau contextual embedding yang mempelajari representasi kalimat secara universal [27]. Contextual embedding yang pertama kali diusulkan adalah Embeddings from Language Model (ELMO) [68] [33], [34], [47], [48], [30], [23], [24], [54], [38], [27], [56], [31], [57], [39], [1], [42], [51], [46], [9] 20…”
Section: Tahap Pembuatan Rencana Awalunclassified
See 1 more Smart Citation